Profiling of FSHR negative allosteric modulators on LH/CGR reveals biased antagonism with implications in steroidogenesis. (15th November 2016) - Ayoub, Mohammed Akli; Yvinec, Romain; Jégot, Gwenhaël; Dias, James A.; Poli, Sonia-Maria; Poupon, Anne; Crépieux, Pascale; Reiter, Eric
Abstract: Biased signaling has recently emerged as an interesting means to modulate the function of many G protein-coupled receptors (GPCRs). Previous studies reported two negative allosteric modulators (NAMs) of follicle-stimulating hormone receptor (FSHR), ADX68692 and ADX68693, with differential effects on FSHR-mediated steroidogenesis and ovulation. In this study, we attempted to pharmacologically profile these NAMs on the closely related luteinizing hormone/chorionic gonadotropin hormone receptor (LH/CGR) with regards to its canonical Gs/cAMP pathway as well as to β-arrestin recruitment in HEK293 cells. The NAMs' effects on cAMP, progesterone and testosterone production were also assessed in murine Leydig tumor cell line (mLTC-1) as well as rat primary Leydig cells. We found that both NAMs strongly antagonized LH/CGR signaling in the different cell models used with ADX68693 being more potent than ADX68692 to inhibit hCG-induced cAMP production in HEK293, mLTC-1 and rat primary Leydig cells as well as β-arrestin 2 recruitment in HEK293 cells. Interestingly, differential antagonism of the two NAMs on hCG-promoted steroidogenesis in mLTC-1 and rat primary Leydig cells was observed. Indeed, a significant inhibition of testosterone production by the two NAMs was observed in both cell types, whereas progesterone production was only inhibited by ADX68693 in rat primary Leydig cells. In addition, while ADX68693 totally abolished testosterone production, ADX68692 had only a partial effect in both mLTC-1 and rat primary Leydig cells. These observations suggest biased effects of the two NAMs on LH/CGR-dependent pathways controlling steroidogenesis. Interestingly, the pharmacological profiles of the two NAMs with respect to steroidogenesis were found to differ from that previously shown on FSHR. This illustrates the complexity of signaling pathways controlling FSHR- and LH/CGR-mediated steroidogenesis, suggesting differential implication of cAMP and β-arrestins mediated by FSHR and LH/CGR. Together, our data demonstrate that ADX68692 and ADX68693 are biased NAMs at the LH/CGR in addition to the FSHR. These pharmacological characteristics are important to consider for potential contraceptive and therapeutic applications based on such compounds.